Functional or emotional? How Dutch and Portuguese conceptualise beer, wine and non-alcoholic beer consumption - Silva, Ana Patricia (2017)
Non-alcoholic beer (NAB) may be a healthier alternative to wine and beer consumption, however has little appeal to consumers. Conceptualisations, i.e. functional and emotional associations that consumers have with foods/beverages, were explored to understand how NAB consumption is perceived, and compared to beer and wine conceptualisations in the Netherlands and Portugal. A qualitative study was performed using a focus group approach with moderate consumers of both countries (n = 56). Content analysis followed by correspondence analysis were used to explore conceptualisations. This study showed similar conceptualisations of the beverages in both countries. NAB has a limited conceptual content, which is mostly functional as a substitute. Beer and wine are rich in both functional and emotional content. Wine is associated with positive low arousal emotional responses, such as calm and loving. Beer is associated with positive high arousal emotional responses, such as adventurous and energetic. NAB evokes neutral and negative emotional responses, such as rational, conscious, and disappointed. The difference in conceptualisations of NAB versus beer/wine might be why NAB is not adopted more widely as a substitute as it does not deliver a comparable emotional response to consumers. NAB should be treated as a beverage in its own right and it might be wise to avoid direct conceptual comparisons with beer. Should the image of NAB be communicated and understood with positive and high arousal associations, such as energetic and convivial, in communication and advertisements, a higher level of congruency between expectation and experience could be achieved.